THE LIGHT-DUTY VEHICLES’ ENERGY EFFICIENCY OPERATIONAL CONTROL METHOD (World Science, 2021)
Considering the relevance of the scientific and technical problem of the light-duty vehicles’ energy efficiency operational control and transportation processes in a market economy, it is necessary to create methods for its solution at different stages of this cycle. The methods of the general use vehicles energy-resource efficiency theory are used to eliminate the paradoxical fragmentation of knowledge about the life cycle stages.Mathematical models of the transport energy efficiency indicators have been developed to meet the operational and technological challenges of the energy-saving reproduction of the road transport services at all stages of the light-duty vehicle life cycle.Based on the models developed, a method is proposed. This method will make it possible to choose a light-duty vehicle with the characteristics corresponding the development of the technical basis of the transport system according to the concept of operational and technological energy saving, and strategies to improve the technical and technological competitiveness of the future transport proposals.